How participatory is participatory heritage management? the politics of safeguarding the Alevi Semah ritual as intangible heritage - (:unkn) unknown (Cambridge University Press, 2013)
This article addresses the shortcomings of UNESCO's intangible heritage program in developing effective mechanisms for community participation in heritage management. Contrary to its original intentions, by prioritizing national perspectives and interests on heritage, UNESCO's program inadvertently allows for strengthening the control of the state over the heritage of minorities and other marginalized groups. This article explores the complexities of state-led intangible heritage management, using the Semah ritual of Turkey's Alevi religious groups as a case in point. I first detail how Alevi voices were silenced during Semah's intangible heritage nomination process, despite those documents submitted by Turkey to UNESCO that claim Alevis' active engagement and full support. Then I discuss in what ways the heritage making of Semah plays into the ongoing efforts of the Turkish government to integrate Alevis into dominant Sunni majority. I conclude by arguing that UNESCO's intangible heritage program, though unintentionally, assists nondemocratic countries in their efforts to force marginalized groups to adopt the mainstream culture. © 2013 International Cultural Property Society.